Assessing the impact of stony coral tissue loss disease on coral cover on Bonaire’s Leeward side - Pepe, Bernardo A.; Van der Roest, Viggo; Vlam, Olivier; Nouse, Sam; Meesters, Erik (Frontiers in Marine Science, 2025)
The effects of stony coral tissue loss disease (SCTLD) in the Dutch Caribbean, specifically in Bonaire, have not been documented since its first sighting in March 2023. By comparing the results of the 2023 surveys with data from previous surveys conducted over the past 9 years, this study quantifies the overall decline in coral cover and investigates the spatial variability of SCTLD’s impact across different subregions of the reef on the leeward side of Bonaire. In the year 2023, a crucial period in the initial phase of the progression of SCTLD, significant reduction in coral coverage was observed, with six key reef-building coral species showing significant vulnerability. Importantly, this research identifies specific subregions that have been disproportionately affected. The insights gained from this study are important for the potential development of specific conservation and restoration strategies for Bonaire, underscoring the necessity for ongoing ecosystem monitoring to safeguard the future of highly sensitive coral reefs in a changing ocean. By advancing our understanding of SCTLD dynamics, this research contributes to the global effort to preserve coral reef ecosystems in the face of emerging coral diseases.